A comparative study of Mobile Network Operators (MNOs) for evaluating network performance at Kolej Tun Gemala - Salleh, Nisrina Syakirah; Mohd Yusof, Mohd Azahari; Rahmat, Mohammad Hafidz (College of Computing, Informatics, and Mathematics, 2025)
The increasing use of mobile networks for internet connectivity shows the importance of evaluating network performance, especially in locations with high user density such as Kolej Tun Gemala. This project focused on addressing connectivity issues faced by students, caused by network congestion and WiFi limitations, by assessing and comparing the performance of three main MNOs: Maxis, U Mobile, and CelcomDigi. Through Android smartphones and network monitoring tools such as Speedtest by Ookla, nPerf, WiFiMan, and Cellular-Z, data on throughput (download and upload), latency, and signal strength were collected during measurements conducted at Levels 1 and 5 of Blocks A and C between 9 pm to 11 pm. Based on network performance results revealed Maxis as the top performer overall, excelling in throughput and signal strength. In contrast, U Mobile shows strong download speeds but experiences latency issues while CelcomDigi demonstrated moderate and balanced performance. This comparative analysis provides actionable insights for students to select suitable MNOs and offers valuable performance to network providers for service improvement. Enhancing mobile network quality in college improves students’ learning experiences and personal development and facilitates better connectivity solutions for enhanced educational networks.